A Greener Future for Surgery: 2024 Research Conference Abstracts - Ledda, Virginia; Nepogodiev, Dmitri; Bhangu, Aneel (Impact Surgery, 2025)
The Research for Greener Surgery Conference took place on 17 December 2024 at the University of Birmingham, attracting 382 in-person attendees and over 350 virtual participants. The event highlighted the urgent need to integrate sustainability into surgical practice, presenting ongoing research efforts funded by the NIHR to create environmentally friendly operating theatres in the NHS. Discussions also focused on local sustainability initiatives within NHS trusts and the broader potential for collaboration and expansion. The conference featured a range of abstracts showcasing local projects across the NHS and Europe, highlighting efforts to make surgery more sustainable. A selection of these abstracts have been published in this special edition of Impact Surgery, offering valuable insights into the practical implementation of sustainability measures at the institutional level.